(untitled) (PHARMACON, 2016)
UJI EFEK ANALGETIKA EKSTRAK ETANOL DAUN LIDAH BUAYA (Aloe vera L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) Cicilia Bertha Uli Lumban Gaol1), Widdhi Bodhi1), Widya Astuti Lolo1) 1)Program Studi Farmasi Fakultas MIPA UNSRAT Manado ABSTRACT The objectives of this research were to find out analgesic effect of ethanol extract of aloe vera leaves with concentration 0,065 g/ KgBB, 0,130 g/KgBB and 0,260 g/KgBB on male rats wistar strain induced thermic. The subject in this research were 15 white male rats wistar which divide into 5 groups, each group consist of 3 white male rats wistar. Negative control group were administered with CMC, positive control group were administered with asetosal, and experiment groups were administered with ethanol extract of aloe vera leaves. Analgesic test were examined by giving pain simulation to treated animals, such a 65oC heat simulation. The response which observed were rats licking hind feet or jumping response. The observation was conducted for 1 minute. Observations were conducted before extract administration, then at 30, 60, 90 and 120 minutes after administered. The results shows that ethanol extract of aloe vera leaves with concentration 0,065 g/ KgBB, 0,130 g/KgBB and 0,260 g/KgBB possess analgesic effect on white male rats wistar, especially concentration 0,260 g/KgBB. Key words : pain, analgesic, aloe vera leaves ABSTRAK Penelitian ini bertujuan untuk mengetahui efek analgetika ekstrak etanol daun lidah buaya dengan dosis 0,065 g/ KgBB, dosis 0,130 g/KgBB dan dosis 0,260 g/KgBB pada tikus putih jantan galur wistar yang diinduksi secara termik. Subjek penelitian ini ialah 15 ekor tikus wistar yang dibagi menjadi 5 kelompok yaitu kelompok kontrol negatif (CMC), kelompok kontrol positif (Asetosal) dan kelompok perlakuan (ekstrak etanol daun lidah buaya). Pengujian efek analgetika dilakukan dengan cara memberikan rangsangan nyeri pada hewan uji, berupa rangsangan panas dengan suhu 65oC. Respon tikus yang diamati yaitu gerakan menjilat kaki belakang dan atau melompat. Pengamatan dilakukan selama 1 menit. Pengamatan dilakukan sebelum pemberian zat uji, kemudian berturut-turut pada menit ke-30, 60, 90 dan 120 setelah pemberian zat uji. Hasil penelitian menunjukkan ekstrak etanol daun lidah buaya dengan dosis 0,065 g/ KgBB, dosis 0,130 g/KgBB dan dosis 0,260 g/KgBB memiliki efek analgetika pada tikus wistar terutama pada dosis 0,260 g/KgBB. Kata kunci : nyeri, analgetika, daun lidah buaya